2020
DOI: 10.21037/tlcr-20-503
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationship of stereotactic body radiotherapy for ultracentral tumor and comparison of efficacy with central tumor: a meta-analysis

Abstract: Background: Ultracentral (UC) tumors, a subset of central lung tumors defined as those that abut the proximal bronchial tree (PBT), have been contraindicated for stereotactic body radiotherapy (SBRT). The present meta-analysis evaluated the efficacy of SBRT for UC and central tumors, and dose-response for local control (LC) of UC tumors. Methods: Databases including MEDLINE and EMBASE were searched up to March, 2020, to identify studies regarding SBRT for UC and/or central tumors. The primary endpoints were LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
4
6
0
Order By: Relevance
“…The most recent meta-analysis of 72 studies of Rim et al demonstrated pooled 1-and 2-year local control rates of 93.3% (95% CI 95.6-8.9%) and 90.4% (95% CI 77.8-96.2%) after SBRT for ultra-central lung tumors, respectively. The corresponding pooled 1-and 2-year overall survival rates were 82.2% (95% CI 71.7-89.7%) and 66.4% (95% CI 51.4-78.7%), respectively [34]. These numbers are in line with our results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The most recent meta-analysis of 72 studies of Rim et al demonstrated pooled 1-and 2-year local control rates of 93.3% (95% CI 95.6-8.9%) and 90.4% (95% CI 77.8-96.2%) after SBRT for ultra-central lung tumors, respectively. The corresponding pooled 1-and 2-year overall survival rates were 82.2% (95% CI 71.7-89.7%) and 66.4% (95% CI 51.4-78.7%), respectively [34]. These numbers are in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…These numbers are in line with our results. When comparing the local control and overall survival rates with the rates for central tumors, to which higher fractionation doses are described in most studies, no differences were found [34]. So, despite the knowledge that a BED 10 of !100 Gy leads to a low local failure rate of 8% compared to a local failure rate of 26% for a BED 10 of <100 Gy [4], our protracted SBRT regimen with a BED 10 of 90-150 Gy leads to somewhat limited, but very decent local tumor control, comparable with that for central tumors.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“… [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] After SBRT, local control (LC) rates of 80.0 % to 97.0 % after two years are comparable to surgical resection. [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] Furthermore, SBRT is increasingly used in oligometastatic cancer patients. [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] Despite major progress in the field of radiation-oncology, the safety and efficacy of SBRT in ultra-central lung tumors remains controversial.…”
Section: Introductionmentioning
confidence: 99%